URGENSI CONTEMPT OF COURT DALAM PELAKSANAAN PUTUSAN PTUN: STUDI PERBANDINGAN INDONESIA DAN THAILAND - Nadiyya, Ahsana (Yustitia, 2022)
The implementation of the decisions of the State Administrative Court (PTUN) in positive law has been strengthened by using administrative and civil coercive measures in the form of imposition of forced money. However, in the decision execution mechanism, the Administrative Court does not have an executive body, so that the State Administration Officer is often disobedient and does not implement the Administrative Court decisions. Thus, citizens' constitutional rights to justice that have been decided by the State Administrative Court can be threatened. This study aims to compare the PTUN system in Thailand and Indonesia and analyze the urgency of contempt of court action. This research uses normative research with a statutory approach and a comparative approach. The results of this study are that there is no regulation regarding the contempt of court and the executorial institutions of the Administrative Court decisions in Indonesia. Meanwhile, Thailand already has a contempt of court regulation and an executive body that functionally carries out the execution of litigants. Therefore, the regulation and implementation of contempt of court to State Administration Officials who do not implement the Administrative Court decisions is an urgency to increase the effectiveness of the execution of Administrative Court decisions in Indonesia.